Successful innovations and lessons learnt in cassava improvement and deployment by IITA in Eastern African Region - Ntawuruhunga, Pheneas; Dixon, A.; Kanju, E.; Ssemakula, G.N.; Okechukwu, R.U.; Whyte, J.; Obiero, H.; Bigirimana, S.; Gashaka, G.; Lukombo, S.; Mkamilo, G.S.; Ndyetabula, I.; et al. (2013)
The International Institute of Tropical of Agriculture (IITA) established its East and Southern Africa Regional Research Centre (ESARC) in Uganda at the former Namulonge Agricultural and Animal Research Institute (NAARI), presently Namulonge Animal and Crops Research Institute (NaCRRI), to address issues of cassava, banana, and plantain development; coordinate all related activities, and work closely with the national agricultural research institutes (NARS). IITA-ESARC began extensive cassava germplasm development to counter the pandemic of African cassava mosaic disease (ACMD) in the region in 1995 through the Eastern Africa Root Crops Research Network (EARRNET). More than 100,000 seeds were evaluated through the conventional plant breeding scheme. Selected genotypes were kept in in-situ conservation from where the regional cassava national programs selected clones for further evaluation in their own countries. Burundi, Democratic Republic of Congo (DRC), Kenya, Rwanda, Tanzania, and Uganda benefited immensely. Through EARRNET, the region gained significantly from the large germplasm base to mitigate the scourge of ACMD and the production of cassava was restored. A new joint effort that was established between Catholic Relief Services and IITA in collaboration with the NARS and other stakeholders promoted the adoption of improved germplasm through participatory variety selection. The breeding approach used enabled to reduce selection period for NARS to release new varieties to farmers as they received elite materials for evaluation. However, the spread of cassava brown streak disease (CBSD) in mid altitude threatened the achievements already made as the new disease attacked most of the ACMD-resistant and high yielding varieties. Its spread in the region calls for more effective collaborative action than before from IITA and its partners to develop new resistant materials to mitigate the effects of both ACMD and CBSD. The present paper attempts to summarize the breeding work efforts made and demonstrate how the germplasm development at this regional center has been useful to the region through effective partnership.